Streptolysin Encoding Genes sagC and sagD as Biomarkers of Fish Pathogen Streptococcus iniae: An In Silico Study - Stalis Norma Ethica; Sri Darmawati; Sri Sinto Dewi; Nurrahman Nurrahman; Ayu Rahmawati Sulistyaningtyas (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2020)
Streptococcus iniae has been notorious as a serious tilapia fish pathogen leading to many disease outbreaks in warm water marine aquaculture. An in silico investigation about the potential of virulence genes of S. iniae, sagC and sagD, as biomarkers of the bacterial species, has been carried out. The aim was to determine bacterial biomarkers, which are important to facilitate early rapid diagnosis of S. iniae streptococcal infection in fish and also in humans. First, specific primers were designed from sagC and sagD genes of S. iniae SF1 genomic DNA using Primer3Plus. Next, in silico PCR (Polymerase Chain Reaction) analysis was carried out using the newly designed primers and 117 genomic DNA of streptococci (all species) retrieved from the database. Primers designed from sagC and sagD genes (SagCF: ‘5- TGCTGACCTCCTAAAAGGGC -3’ and SagCR: ‘5- CTATGCGGCGGGTTTAAGGT -3’ as well as SagDF: 5’- GCCAATCCAATCCTGTCATGC -3’ and SagDR: 5’- TGCAGCTTCCATAACCCCTC -3’) could result in a single band of each matching to 558-bp and 590-bp PCR products only from S. iniae. From 116 other streptococcal genomes studied using similar primers have resulted in no amplicon bands. A further check showed that the amplicons were truly part of sagC and sagD genes of S. iniae. These results showed that sagC and sagD genes appeared to be biomarkers of S. iniae, which are potential to be used to facilitate rapid diagnostic of the pathogenic bacterium.